PEMANFAATAN APLIKASI JUST REMINDER SEBAGAI MEDIA DALAM UPAYA TAQARRUBILALLAH DI ERA SOCIETY 5.0 - Taschiyatul Hikmiyah (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Equitable use of gadgets does not guarantee that all users can operate them only in positive terms. Therefore, the writing of this work is intended as a form of using the